High-Speed Rail (HSR) Users and Travel Characteristics in Turkey. (2017) - Celikkol-Kocak, Tümay; Dalkic, Gülçin; Tuydes-Yaman, Hediye
Abstract: To change the current road dominancy in the intercity passenger transportation, Turkey has been establishing High-Speed Rail (HSR) services as a competitive mode since 2009. A user survey was conducted at four stations of the currently serving HSR lines to obtain data on i) intercity mode choices of HSR users for different trip purposes, ii) alternative modes preferred in HSR corridors and iii) user perspectives on modal service attributes (i.e. travel time, cost, safety, etc.). A significant share of first-time HSR users showed the growing demand of HSR as a transportation mode in Turkey. There were many business or education related trips observed. In the short corridors (i.e. Ankara-Eskişehir), the modal shift was mainly from road transportation, while in Ankara-Istanbul corridor, shift from air to HSR was also observed.